Should Off-Label Medicines Be Included in the Universal Health Coverage (UHC) Schemes? Why, When, and How? - Mulyani, Ully Adhie (Pusat Penelitian dan Pengembangan Sumber Daya dan Pelayanan Kesehatan, 2017)
Off label medicine refers to any medicine that is used to treat any ailment beyond of its approved / licensed indication by National Regulatory Authorities, such us FDA in USA and BPOM in Indonesia. Off-label medicines are used because the available and approved drugs do not have the desired effect, then doctors try medicine that have not been licensed indications. Some other reasons in practice off-label medicines use and prescribing are that drugs in the same category have the same effect (although have not been approved by indication); the expansion to a lighter form than the licensed indication, or extension of use for certain related conditions. At the opposite, the disadvantage of the practice off-label medicine use is generally not included in any health insurance benefit package, also not covered by mandatory insurance scheme (JKN-BPJS). Patients should pay for the price of a drug that has not been assured or proven of its efficacy and safety. It needs strong evidence based on scientific research to ensure the safety and effectiveness of off-label medicines to be included in the list of medications (national formulary) to put it on National Health Insurance (BPJS) benefit package.